Requirements and Design Strategies of Chronic Disease Mobile Applications - Zahra, Fatima; Mohd, Haslina; Hussain, Azham; Omar, Mazni (2018)
Despite the huge amount of currently available chronic disease applications, the functionalities offered are limited and do not capture the real users’ requirements. Patients and physicians should be directly involved in the application development to tackle the lack of usability and users’ requirements especially for the chronic illness target group. Even though, the use of mobile applications to monitor health and chronic health conditions is gaining popularity but their effectiveness in managing disease is still lacking. Consequently, such applications are usually being misused or underutilized, which lead to the failure of meeting the development objective. Nevertheless, it is believed that the future of the mobile health applications development is presumably optimistic. Therefore, the objective of this study is to identify the related requirements and design strategies which are often neglected while designing the chronic disease mobile applications. A systematic literature review (SLR) has been conducted based on 60 journal and conference proceeding articles from various established journal and conferences proceeding such as IEEE, ACM,Science Direct, JMIR and other established medical journals. To strengthen the findings form the SLR, real users were also interviewed to ensure the usability and requirements of the chronic disease applications follow accordingly to the users’ needs.The merging of these two strategies helps to determine the usability dimensions which provide the basis for developing a usability evaluation model as the next part of this study.